Initial Development and Factor Structure of the Educator Test Stress Inventory. (June 2015) - von der Embse, Nathaniel P.; Kilgus, Stephen P.; Solomon, Hadley J.; Bowler, Mark; Curtiss, Caroline
With the proliferation of test-based accountability policies, educators and students alike are under pressure to improve test performance. However, little is known regarding the stress experienced by educators in response to these policies. The purpose of this article is to describe the initial development and validation of a new measure of stress associated with high-stakes testing. Psychometric properties were examined within a sample of 8, 084 educators in a southeastern state in the United States. An exploratory and confirmatory factor analysis of the Educator Test Stress Inventory supported a bifactor model of teacher test stress, with one general factor of Total Teacher Stress and two narrow factors of Sources of Stress and Manifestations of Stress. This study is an important first step in establishing a reliable and valid measure of teacher stress and better understanding the impact of high-stakes testing and educational accountability policies. Implications for the assessment and intervention of teacher stress are discussed.